Rotating Algae Biofilm Reactor for Management and Valorization of Produced Wastewater - Wood, Jonathan L.; Takemoto, Jon Y.; Sims, Ronald C. (Frontiers in Energy Research, 2022)
Production and enhancement of high value phycocyanin pigment from microalgae biofilms cultured on oilfield and natural gas produced wastewater were investigated. Cyanobacteria isolated from Logan City, Utah, wastewater treatment Lagoons (LLC2) was cultured in produced water using rotating algal biofilm reactors (RABRs). The RABRs were operated under “low” and “high” light conditions and biomass and phycocyanin content were compared. Phycocyanin content was enhanced by growth under low light conditions to a maximum yield of 31.7 mg/g ash-free dry weight (AFDW) biomass for an 87.6% increase in phycocyanin yield. Phycocyanin productivity was equivalent for both the low and high light treatments (327±81 and 305±39 mg/m2/day, respectively), due to the significantly lower AFDW biomass productivity of the low light treatment (2.7±0.4 g/m2-day). An indoor laboratory evaluation of 14 substrata for biofilm growth showed that cotton rope and cotton belt material provided the highest biomass yields. Further evaluation in a pilot-scale outdoor produced wastewater pond showed that the biomass characteristics from the two substrata differed. The corrugated surface area of the cotton rope cultured a biofilm with a large community of non-photosynthetic organisms with an autotrophic index of 507 and a low phycocyanin yield of 3.4 mg/g AFDW. However, the cotton belt substratum cultured a healthy photosynthetic biofilm with an autotrophic index of 127 and a phycocyanin yield of 47.0 mg/g AFDW. These results demonstrate the cultivation of microalgae biomass and valorization of oilfield and natural gas produced wastewater through the design and management of algal-based biofilm photobioreactors.